The Women's Division of the Democratic State Central Committee luncheon invitation (1968)
An invitation from the Women's Division of the Democratic State Central Committee to an Award Luncheon honoring Democratic workers. The luncheon was held at noon on Friday, April 26, 1968, at the Ambassador Hotel in Los Angeles, with Secretary of Labor Willard Wirtz as the guest speaker and a $6.50 contribution requested. It lists luncheon co-chairmen, including Jane Tolmach as Chairman-South, along with honorary chairmen and members of the luncheon committee.